Efficient Low Driving Force Charge Separation in an Electron Deficient Zn-Porphyrin-Fullerene Donor-Acceptor Conjugate - Wolf, Maximilian; Costa, Joana I. T.; Minameyer, Martin; Drewello, Thomas; Tome, Augusto C.; Guldi, Dirk Michael (Journal of Physical Chemistry C, 2019)
Here, we present a novel conjugate based on a weakly electron-donating Zn(H)-meso-tetrakis(pentafluorophenyl)porphyrin linked to a strongly electron-accepting C-60. From spectroscopic and electrochemical investigations a 1.9 eV high charge-separated state is derived. Transient absorption spectroscopy measurements analyzed by global target analysis confirmed the successful charge separation with a quantum yield of 72% despite an overall small driving force of only 0.2 eV. The charge separated state lifetime is in the nanosecond range. Considering that 90% of the singlet excited state energy is transiently stored in the charge-separated state, we conclude a charge separation energy efficiency of 65%.
CRIS-Team WoS Importer:2019-12-13